Arbuscular Mycorrhizal Fungi Associated with Myrciaria dubia in the Amazonia Region, Peru - Alexandra Jherina Pineda-Lázaro; Adela Vallejos-Tapullima; Angel David Hernández-Amasifuen; Santos Carballar-Hernández; Sixto Imán-Correa; Fernando Marcelo Carvajal-Vallejos; Orlando Ríos-Ramírez; Mike Anderson Corazon-Guivin (Advances in Agriculture)
Myrciaria dubia (Kunth) McVaugh (camu-camu) is a shrub native to the Amazon region that produces fruits with a high content of vitamin C and various bioactive compounds, making it a functional food with antioxidant, anti-inflammatory, and antimicrobial properties. However, it is unknown which microorganisms are associated with its root system and can influence its growth and productivity. Arbuscular mycorrhizal fungi (AMF) are associated with most plants and are essential for their establishment, survival, and productivity since they facilitate their nutrition, increase water absorption, and improve soil structure. Although the AMF association is already known in some species of Myrciaria, no report is available on its association in M. dubia. This study presents, for the first time, the symbiotic association between AMF and M. dubia from the INIA San Roque experimental station located in the Amazon region, Peru. For the morphological and molecular analyses of the AMF, samples of rhizospheric soil and roots from two native accessions of the National Germplasm Bank of M. dubia were collected. Eighteen AMF morphospecies were identified in rhizospheric soil, belonging to nine genera Acaulospora, Ambispora, Entrophospora, Diversispora, Gigaspora, Glomus, Paraglomus, Funneliformis, and Sclerocystis, being the first one the most frequent. The roots of M. dubia showed high colonization by AMF (mean = 91%), and characteristic structures of arbuscular mycorrhizae, such as vesicles, hyphae, and arbuscules, could be observed. Likewise, the molecular analysis detected the presence of genetic material (rDNA) corresponding to AMF in the roots of both accessions. Our results evidenced the symbiotic association between AMF and M. dubia, which encourages further investigation of the functional potential of these microorganisms in this economically crucial agricultural plant in Peru.